2015
DOI: 10.1016/j.jrras.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and simulated study of detector collimation for a portable 3″ × 3″ NaI(Tl) detector system for in-situ measurements

Abstract: The effect of detector collimator and scatterer thickness on multiple Compton backscattered gamma photons is studied. Gamma photons from a 137 Cs source of 5.8 mCi, is allowed to fall on Carbon, Aluminium, Iron and Copper targets and the scattered photons are detected by a properly shielded 76 mm  76 mm NaI(Tl) scintillation detector located at 90 to the incident beam. To extract the contribution of multiple scattered photons from the measured spectra, single scattered distribution is remodelled analytically.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…where Q-gamma radiation source intensity, 1/sec, h-distance from gamma radiation source to the irradiated surface, m, dxdy-area element in Cartesian coordinate system, m 2 .…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…where Q-gamma radiation source intensity, 1/sec, h-distance from gamma radiation source to the irradiated surface, m, dxdy-area element in Cartesian coordinate system, m 2 .…”
Section: Results and Analysismentioning
confidence: 99%
“…Analysis of the results of studies and publications on the control of iron content in ore arrays using LS in wells showed that in most cases insufficient attention is paid to the issues of measurement accuracy [1]. Nuclear physics methods for determining the content of the useful component in the ore were considered in works [2][3][4], where attempts were made to improve the accuracy of measurements depending on the number of gamma quanta reflected from the surface of the absorber. In work [5], the parameters of scintillation sensors for recording scattered gamma quanta are considered.…”
Section: Introductionmentioning
confidence: 99%